1973
DOI: 10.1111/j.1755-3768.1973.tb08244.x
|View full text |Cite
|
Sign up to set email alerts
|

Pseudoexfoliation of the Lens Capsule and Liberation of Iris Pigment

Abstract: A total of 220 inmates of old people's homes, all over 60 years of age, were examined for pseudoexfoliation of the lens capsule. The incidence recorded for the age group 60-69 years was 10°/o, 70-79 years 21.3O/o and 80-89 years 32.8 "/a. The intraocular tension of the eyes with pseudoexfoliation averaged 17.5 mmHg, against an average of 15.4 mmHg in normal eyes. After mydriatics, pigmented floaters were seen in the aqueous humour of 61.5 O / o of the normal eyes, and 83.3 "/o of the eyes with pseudoexfoliatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
23
1
8

Year Published

1976
1976
2011
2011

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(36 citation statements)
references
References 12 publications
4
23
1
8
Order By: Relevance
“…Krause et al (1973) found the IOP to be higher in eyes with PEX when compared to PEX-negative eyes, similar results were obtained by Madden & Crowley (1982). Krause et al (1973) reported increased liberation of iris pigment in PEX-positive eyes implying that this might lead to trabecular blockage. Similar results were reported by Mapstone (1981).…”
supporting
confidence: 83%
“…Krause et al (1973) found the IOP to be higher in eyes with PEX when compared to PEX-negative eyes, similar results were obtained by Madden & Crowley (1982). Krause et al (1973) reported increased liberation of iris pigment in PEX-positive eyes implying that this might lead to trabecular blockage. Similar results were reported by Mapstone (1981).…”
supporting
confidence: 83%
“…The mean age of the responder group, 62.3 years, was a few years lower than the mean age of the total series. In the PE group, too, the mean Visual field Leydhecker 1973), similarly P E (Tarkkanen 1962;Aasved 1971;Krause 1973;Krause et al 1973;Forsius et al 1974 (Table I). Marked IOP elevations and concurrent liberation of profuse pigment in the aqueous were reported by Kristensen (1965Kristensen ( , 1968) during mydriasis test with sympathomimetics on some eyes with capsular glaucoma under treatment.…”
Section: Discussionmentioning
confidence: 80%
“…For example, ES prevalences among Icelanders, Finns, and Lapps are greater than 20%. 32,34,56,57 One explanation may be that the extracellular deposits of ES represent a nucleation reaction 58 that is prone to develop at lower temperatures. While the temperature in the vascular iris may be close to the core body temperature, the temperatures in the avascular ocular segments, such the anterior chamber and lens, may be susceptible to ambient temperatures.…”
Section: Discussionmentioning
confidence: 99%